Inhaled methoxyflurane (Penthrox) use in the outpatient and ambulatory setting: a systematic review - Paul Smith; T Justin Clark; Prathiba M De Silva; Bibi Zeyah Fatemah Sairally (BMJ Open)
Objective We assessed whether Penthrox (methoxyflurane) can provide better pain relief for elective, outpatient interventional procedures compared with other methods of pain control.Design Systematic review.Data sources Cochrane Central Register of Controlled Trial, MEDLINE, Emcare, Embase, ClinicalTrials.gov and the Cumulative Index to Nursing and Allied Health Literature were searched from inception to 6 November 2023.Eligibility criteria All published studies including randomised controlled trials (RCTs), cohort studies and case–control studies investigating Penthrox for pain relief, during and/or after an interventional procedure, were included.Data extraction and synthesis Two independent reviewers identified eligible studies and retrieved data. Risk of bias was assessed using Cochrane Collaboration Risk of Bias V.2.0 and Risk of Bias in Non-randomised Studies of Interventions (ROBINS I) tools. A meta-analysis was not possible due to heterogeneity.Results The literature search yielded 1189 records. 12 studies were eligible for inclusion: 5 RCTs and seven non-randomised studies of interventions (NRSIs). Penthrox was used for a range of procedures across five medical specialities: gastroenterology, gynaecology, haematology, orthopaedics and urology. Two RCTs showed a significant reduction in intraprocedural pain when Penthrox was compared with placebo. However, three RCTs where Penthrox was compared with either placebo or intravenous sedation showed no significant differences in pain or comfort level. Similarly, the NRSIs showed variable results. Most patients were satisfied (63% to >98%; seven studies) with Penthrox, and seven out of eight studies reported that the majority of participants would use it again (46.8%–95%; eight studies). No serious adverse events were reported.Conclusion Penthrox (methoxyflurane) shows promise as an analgesic for invasive, elective interventional procedures in the outpatient setting, although the relative benefits appear to vary depending on intervention and comparator pain control measures. There is a pressing need for robustly conducted, large, generalisable multicentre RCTs to evaluate the effectiveness of Penthrox.PROSPERO registration number CRD42023404574.